(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Gallstone diseases remain a common health problem for human, affecting millions of people throughout the world. In Iraq, recent years has shown an increasing number of patients with gallstones with concurrent decreasing age of presentation, risk factors have been assessed taking in consideration the effect of stressful life events that Iraqi peoples had been suffered during these years on the development of gallstone diseases. Objective:To give an idea about, and possible causes for the changing in number, age of presentation and trend of surgical management of gallstone diseases in Iraq. Methods: Clinical assessment and risk factors assay including stressful life events were done for 1226 patients who have been cholecystectomised over seven years from Jun 2002 to Jun 2009 in Al-kadhimiya Teaching Hospital. Results:Significant increases in the number of symptomatic gallstone cases were noted, nearly 50% of them presented with abdominal pain, more than half of patients were young in the 3rd and 4th decades, female to male ratio was 5.9:1 and decreasing with age, 74% of patients had BMI > 25% (over weight), impact of stressful life event was obvious in the recent years on nearly two third of patients with gallstone diseases, minimal invasive technique (laparoscopic surgery) was evolving and most of the cases now done by this method. Conclusions:Gallstones diseases are increasing in our country with obvious decrease in the age of presentation, this might be due to stressful life events to which Iraqi peoples had been exposed, and also the revolution of minimal invasive surgery had a great impact in the management of this disease. Key words:Pattern, Incidence, Gallstone diseases.